The Analysis of the Song Lyrics of the Energy of Asia Music Album from the Perspective of Systemic Functional Grammar - Septyana Atik Purwandari; Didin Nuruddin Hidayat; Waliyadin Waliyadin; Muhammad Syafii S (Institut Agama Islam Negeri Palopo, 2022)
Music has played a role as the media in modern society. It is used not only to be listened to accompany in doing activities but also as the media to inform people about what is happening around them. This study aims to investigate the most frequent occurrence of mood system and adjunct of each lyric and describe the modality realized in the lyric of Energy of Asia’s album of the 2018 Asian Games, to find the transitivity processes, and to find the textual meaning (theme) of the song lyrics. In this descriptive qualitative research, three song lyrics from the